Comparative secretomic and proteomic analysis reveal multiple defensive strategies developed by Vibrio cholerae against the heavy metal (Cd2+, Ni2+, Pb2+, and Zn2+) stresses - Zhang, Beiyu; Xu, Jingjing; Sun, Meng; Yu, Pan; Ma, Yuming; Xie, Lu; Chen, Lanming (Frontiers in Microbiology, 2023)
Vibrio cholerae is a common waterborne pathogen that can cause pandemic cholera in humans. The bacterium with heavy metal-tolerant phenotypes is frequently isolated from aquatic products, however, its tolerance mechanisms remain unclear. In this study, we investigated for the first time the response of such V. cholerae isolates (n = 3) toward the heavy metal (Cd 2+ , Ni 2+ , Pb 2+ , and Zn 2+ ) stresses by comparative secretomic and proteomic analyses. The results showed that sublethal concentrations of the Pb 2+ (200 μg/mL), Cd 2+ (12.5 μg/mL), and Zn 2+ (50 μg/mL) stresses for 2 h significantly decreased the bacterial cell membrane fluidity, but increased cell surface hydrophobicity and inner membrane permeability, whereas the Ni 2+ (50 μg/mL) stress increased cell membrane fluidity (p < 0.05). The comparative secretomic and proteomic analysis revealed differentially expressed extracellular and intracellular proteins involved in common metabolic pathways involved in the V. cholerae isolates to reduce cytotoxicity of the heavy metal stresses, such as biosorption, transportation and effluxing, extracellular sequestration, and intracellular antioxidative defence. Meanwhile, different defensive strategies were also found in the V. cholerae isolates to cope with different heavy metal damage. Remarkably, a number of putative virulence and resistance-associated proteins were produced and/or secreted by the V. cholerae isolates under the heavy metal stresses, suggesting an increased health risk in the aquatic products.